Urinary function and health-related quality of life of patients after laparoscopic radical prostatectomy: two methods of assessment for 112 patients with up to six years of follow-up. (January 2013) - Kass-Iliyya, Antoine; Vasdev, Nikhil; Soomro, Naeem; Durkan, Garrett C
Background: Wide variation exists between methods of assessment of urinary function following laparoscopic radical prostatectomy (LRP). Objective: To assess post-operative urinary function and quality of life (QOL) after LRP using validated questionnaires and compare these results with subjective assessments obtained during outpatient consultations. Design, setting and participants: Between January 2004 and December 2009, 200 men with organ-confined prostate cancer underwent LRP at our centre. Post-operative urinary function and QOL were evaluated using validated questionnaires (ICIQ-MLUTS and FACT-P). Data regarding urinary function, which were collected at the outpatient clinic (OPC), were also available for these 112 patients. Outcome measurements and statistical analysis: Objective post-operative urinary function obtained from validated questionnaires using univariate and multivariate logistic regression models to evaluate the impact of urinary symptoms on QOL. Results and limitations: Based on the validated questionnaires, 75% (75/112) of patients had low incontinence scores (0 to 8/24) at a mean follow-up of 37 months. On subjective assessment at the OPC, 82% (92/112) of patients were considered dry (pad free). The majority of patients had a high QOL score (109–156), indicating good quality of life. Urinary symptoms' severity was significantly correlated with QOL, where severe symptoms were associated with lower QOL. A literature search revealed wide discrepancies in the assessment of functional outcomes following LRP rendering comparison between studies extremely difficult. Conclusions: The functional outcomes of LRP vary depending on the assessment used. There continues to be a lack of congruity between the methodologies used in the literature and few studies published have used validated questionnaires.